Evaluasi Implementasi SAP Modul Material Management: Studi Kasus pada PT Bumitama Gunajaya Agro - Santo Fernandi Wijaya; Yustina Handoyono (Bina Nusantara University, 2012)
An integrated information system is a necessity for a company to help solve problems in business transactions management. SAP application is an application that is able to provide solutions to such problems. The purpose of this study was to evaluate the running business processes on the Material Management module; evaluate the performance of the running SAP systems associated with the implementation and maintenance of SAP applications as well as to give sugestions based on the development of evaluation results obtained, in terms of business processes, performance, and financial. Utilized for analysis is IT Balanced Scorecard method, while ASAP (Accelerated SAP) method is used for the system development. This study produced an analysis of the evaluation of the enterprise business processes in implementing the SAP development of ERP system modules Material Management.